Understanding How Infrared Beak Treatment Affects the Beak Tissue and the Healing Response of Brown and White Feathered Layer Pullets - Sarah Struthers; Ashish Gupta; Susantha Gomis; Eugenia Herwig; Karen Schwean-Lardner (Animals, 2019)
Infrared beak treatment has less of a negative impact on laying hen welfare compared to other methods of beak treatment; however, it is still not fully understood how infrared beak treatment affects the beak tissue during the first few days post treatment. The objective of this study was to examine the histology of infrared beak treated vs. untreated beaks of 2 strains of layer chicks during early life. One-hundred Lohmann Brown-Lite (LB) and 100 Lohmann LSL-Lite (LW) chicks were obtained; 50 chicks per strain were infrared beak treated post hatch (IR) with the remainder being sham untreated controls (C). Data collected included presence of beak sloughing, length, and histology. Histology slides were analyzed and scored on a scale of 0 to 4, with 0 indicating no lesions and 4 indicating severe inflammation. Sloughing of the treated beak tissue began at 10 days and was complete by 20 days. IR pullets had shorter beak lengths once sloughing was initiated and less overall beak growth. No differences in healing scores were found between treated LB and LW beaks; all treated LB beaks were healed by 21 days while some LW beaks still showed inflammation. Overall, infrared beak treatment was effective at reducing beak growth post treatment. Healing occurred post treatment in both strains as evident by complete regeneration of the epithelium and a reduction in inflammation.